Invasion dynamics of competing species with stage-structure. (21st December 2017) - Bewick, Sharon; Wang, Guoqing; Younes, Hannah; Li, Bingtuan; Fagan, William F.
Highlights: A spatially explicit, stage-structured Lotka–Volterra competition model is proposed. Using heuristic arguments, we obtain approximate asymptotic spread speed solutions. Adding stage structure alone is insufficient to alter predicted spread speeds. Accompanied by specific heterogeneities, stage structure does alter spread speeds. Abstract: The spread of an invasive species often results in a decline and subsequent disappearance of native competitors. Several models, primarily based on spatially explicit Lotka–Volterra competition dynamics, have been developed to understand this phenomenon. In general, the goal of these models is to relate fundamental life history traits, for example dispersal ability and competition strength, to the rate of spread of the invasive species, which is also the rate at which the invasive species displaces its native competitor. Stage-structure is often an important determinant of population dynamics, but it has received little attention within the context of Lotka–Volterra invasion models. For many species, behaviors like dispersal and competition depend on life-stage. To describe the processes of invasion in these species, it is important to understand how behaviors that vary as a function of life-stage can impact spread rate. In this paper, we develop a spatially explicit, stage-structured Lotka–Volterra competition model. By comparing spread speed predictions from this model to spread speed predictions from an analogous single-stage model, we are able to determine when stage-structure is important and how stage-dependent behavior can alter the characteristics of an invasion.